Energy convergence of shock waves and its destruction mechanism in cone-roof combustion chambers. (1st November 2016) - Xu, Han; Yao, Anren; Yao, Chunde; Gao, Jian
Highlights: Experiments with simulations are designed to probe into engine severe knock. Energy convergence at central and edge region is observed in closed-limited space. Modes with different intensities and mechanism of energy convergence are revealed. Chamber shape and equivalence ratio can affect the energy convergence. The destruction effects of energy convergence on pistons are recognized. Abstract: Energy convergence is considered as an important phenomenon in internal combustion engines under severe knock, in which shock waves caused by violent combustion may aggregate the energy released by fuel burning to damage engine parts like pistons and spark plugs easily. In order to reveal such convergence mechanism and its destruction effects, a novel detonation bomb experiment combined with numerical simulations are conducted. In bomb experiments, a detonation wave is forcibly introduced into a clearance-variable cone-roof combustion chamber by a high energy spark ignition. Four pressure transducers were installed in different positions to monitor the energy convergence. Combined with the experiments, numerical simulations were conducted to reveal the convergence modes and mechanisms. Finally, destruction samples were presented to validate this research. It's found that the energy convergence of shock waves always occurs in middle and edge region, which are vulnerable to be damaged. Three modes of energy convergence are concluded for middle region while several ways of energy convergence are concluded for edge region, which are all related with the chamber shape and may result in different levels of convergence. It's also found that though detonation strength (knock intensity) can be changed by both equivalence ratios and initial pressures, only the equivalence ratios can change the convergence modes while the initial pressures cannot.